Malformation of a Mesocolon as a Cause of Colic in an Arabian Foal - Bernard Turek; Elżbieta Stefanik; Natalia Kozłowska; Olga Drewnowska-Szczepakowska; Kamil Górski; Julia Mickiewicz (Veterinary Sciences, 2021)
This paper describes a case of partial lack of the mesocolon in a 7-month-old colt. The foal was referred to the hospital with clinical signs of severe abdominal distension of a few hours duration. Because analgesics did not relieve pain, the foal remained uncomfortable, and distension of the abdomen increased; an exploratory laparotomy was performed under general anaesthesia in dorsal recumbency. The final diagnosis was confirmed intraoperatively. During exploration of the abdominal cavity, other problems like right dorsal displacement and torsion of the colon were recognized. Correction of all problems was completed, and the mesentery was sutured. Recovery from anaesthesia was uneventful. The foal was recovering well a few months after surgery, and the owner did not complain about the results of the treatment.